Zeolite-supplemented diets in the prenatal period affected postpartum reproductive parameters, colostrum production, and body condition score of dairy cows (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: The effect of zeolite on Ca plasma concentration, reproductive parameters, body condition score (BCS), and colostrum properties was evaluated in Holstein dairy cows during the postpartum period. Materials and Methods: Sixty pregnant cows were allocated to three experimental groups, including 1) a control (CON) diet; 2) a CON diet + 0.75% dry matter (DM) zeolite (100 gm/day/ cow); and 3) a CON diet + 1.5% DM zeolite (200 gm/day/cow). Experimental diets were fed to cows during the last 4 weeks of pregnancy. Blood sample evaluation for Ca concentration was done. The prevalence of hypocalcemia and reproductive parameters, including BCS and colostrum properties, was also measured. Results: Total Ca and ionized calcium (Ca++) concentrations in plasma at 6 and 12 h after calving were higher in zeolite-consuming cows than those in CON s (p < 0.01). Mean frequencies for severe and subclinical hypocalcemia in zeolite-consuming cows were 11.64% and 19.36% lower than those in the CON group, respectively (p < 0.01). The mean pregnancy efficiency of these cows was also 12.94% higher than the CON (p < 0.01). The mean BCS (p ≤ 0.05) and colostrum quality (p < 0.01) of zeolite-consuming cows were at maximum, but their mean colostrum yield was lower than that of the CON group (p < 0.01). Conclusion: Zeolite dietary supplementation at levels of 0.75% and 1.5% DM of the periparturient diet is recommended for better CON of hypocalcemia, improved BCS and colostrum quality, and better prevention of postpartum reproductive disorders in dairy cows.J. Adv. Vet. Anim. Res., 10(3): 410–420, September 2023http://doi.org/10.5455/javar.2023.j694